2017
DOI: 10.1080/24750573.2017.1304748
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a school-based, teacher-delivered psychological intervention group program for trauma-affected Syrian refugee children in Istanbul, Turkey

Abstract: Objective: The purpose of this study was to evaluate an innovative, protocol-based, group cognitive behavioral therapy (CBT) program delivered by trained teachers to reduce emotional distress and improve psychological functioning among the war-traumatized Syrian refugee students living in Istanbul. Methods: A total of 32 participants, aged between 10 and 15 years (mean = 12.41, SD = 1.68) and mostly females (m/f = 12/20) were randomly selected from a sample of 113 refugee students based on their trauma-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 31 publications
1
53
0
3
Order By: Relevance
“…Aside from testing the modalities with Syrian refugee children, intervention studies provide useful descriptive information. In this particular study (Gormez et al, 2017), overall, all children reported having been exposed to or having witnessed traumatic events. About 75% of them experienced a warrelated killing of a loved one, 88.7% of them left one or more loved ones in Syria, and 46.7% of them witnessed, and 32.3% directly experienced, torture or cruelty.…”
Section: Intervention In the Context Of Syrian Refugee Childrenmentioning
confidence: 77%
“…Aside from testing the modalities with Syrian refugee children, intervention studies provide useful descriptive information. In this particular study (Gormez et al, 2017), overall, all children reported having been exposed to or having witnessed traumatic events. About 75% of them experienced a warrelated killing of a loved one, 88.7% of them left one or more loved ones in Syria, and 46.7% of them witnessed, and 32.3% directly experienced, torture or cruelty.…”
Section: Intervention In the Context Of Syrian Refugee Childrenmentioning
confidence: 77%
“…Most school-based mental health interventions are delivered by mental health specialists (social workers, psychologists, counselors, or other support staff). However, one study developed a group-based cognitive-behavioral therapy intervention to be delivered by teachers to war-traumatized Syrian refugee children living in Istanbul, Turkey (Gormez et al, 2017). Due to a lack of resources and the challenges of recruiting Arabic-speaking mental health professionals in Turkey, the research team opted to train existing teachers to deliver an eight-week (70-90 minutes per session) group CBT intervention.…”
Section: Mental and Behavioral Healthmentioning
confidence: 99%
“…It was also challenging to nd a psychiatrist who would embrace the task-sharing model, which aims to deliver interventions that do not depend upon psychiatrists as the service providers. Over 6 months, the U.S. and Kosovar investigators were able to identify a child and adolescent psychiatrist, Dr. Vahdet Görmez, who is also a certi ed trainer in cognitive behavioral therapy (CBT), conducted research with Syrian adolescent refugees in school setting in Istanbul [31][32] who became our primary partner. The main argument in deciding to collaborate with Dr. Görmez was his practical experience in working with Syrian refugees in school setting and his interest in refugee mental health.…”
Section: Lack Of Focus On Task-sharingmentioning
confidence: 99%